Women's Study as an Alternative Islamic Education in Building Social Harmonization - Susiyati Ningsih; Ulil Hidayah (al-Afkar, Journal For Islamic Studies, 2026)
This research aims to analyze the contribution of women's recitation as an alternative form of Islamic education in building social harmonization. The research uses a qualitative approach with observation, interview and documentation techniques in the women's study community. The results of the research show that women's recitation plays a role in strengthening moderate religious literacy, building social solidarity, and creating an inclusive space for dialogue. This role has implications for the formation of collective awareness to maintain harmony and strengthen community cohesion. Thus, women's recitation has a strategic position as an alternative model of Islamic education that is relevant in the context of strengthening social harmonization.